A Qualitative Analysis of the Driving Forces behind the Nikshay Mitra in National Tuberculosis Elimination Program of India - Ravindra Nath; Aninda Debnath; Vidushi Rathi; Pranav Ish; Kanishk Sinha (Journal of Advanced Lung Health)
Introduction: The Nikshay Mitra initiative under our national program in India allows citizens to adopt and support tuberculosis (TB) patients by providing additional nutritional, diagnostic, and vocational assistance. Materials and Methods: This study is a cross-sectional qualitative analysis based on data extracted from the Central TB Division website, which houses feedback from Nikshay Mitras who adopted TB patients. Results: Thematic analysis carried out identified five major themes that serve as the reason for motivations for citizens to become Nikshay Mitras: altruism and compassion, professional responsibility and knowledge, government initiatives and national duty, personal experience with TB, and addressing TB stigma. Conclusions: The motivations to become Nikshay Mitras are diverse, ranging from compassion for the poor to professional responsibility and a desire to support national health goals. These factors should be leveraged for expanding the Nikshay Mitra initiative among the family members of TB patients as well.